Implications of Using Artificial Intelligence Applications on The Principle of Kafa'ah From The Perspective of Fiqh Munakahat - Fathur Rahmi; Ashabul Fadhli (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2026)
This study explores the influence of Artificial Intelligence (AI)-based matchmaking platforms on the principle of kafa’ah viewed through the lens of fiqh munakahat. The acceleration of modernization, marked by the extensive integration of internet technologies, has encouraged a transition from traditional to digital methods in choosing life partners. AI-assisted matchmaking introduces a more adaptive and efficient mechanism for identifying preferred partner criteria. Employing a qualitative, descriptive–analytical approach, this study relies on library research. Primary data derive from both classical and contemporary Fiqh works that elaborate on the notion of kafa’ah within fiqh munakahat. In contrast, secondary data consist of journal articles and related academic sources. The analysis utilizes the maslahah framework to evaluate the contextual relevance of kafa’ah in the digital era. The findings indicate that AI matchmaking applications can serve as legitimate innovations for partner selection in the modern context, as long as they remain aligned with the legal foundations of fiqh munakahat concerning kafa’ah. The intersection between empirical technology and normative Islamic law opens a meaningful dialogue between traditional jurisprudence and emerging digital realities. Consequently, this research contributes to a more comprehensive public understanding of how AI technology may be utilized responsibly without compromising sharia principles